Edukasi Perilaku Hidup Bersih dan Sehat dan Pengembangan Media Flash Card pada Guru SD wilayah Kecamatan Kerjo Karanganyar - Dyonisa Nasirochmi Pakha; Ida Nurwati; Muthmainah Muthmainah (Smart Society Empowerment Journal, 2024)
Introduction: Teachers as role model need to encourage perilaku hidup bersih dan sehat (PHBS) – meaning clean and healthy lifestyle – in schools and teach it to students, leading to a healthy environment. Several elementary school teachers in Kerjo District have not been habituated to optimally implementing PHBS. The aim of this community service is to conduct PHBS education and develop flash cards; thus, this may increase understanding of PHBS, then apply these lifestyles optimally.Methods: The community service was carried out by counselling PHBS on Tuesday, 23rd May 2023. The target was elementary school teachers in the Kerjo District, involving 27 elementary schools with 44 participants. Data was collected from 27 schools for classifying PHBS strata, then the participants took pre-test and post-test to measure level of knowledge. Next, counselling was carried using interactive lecture and flash card. The distributed flash cards were also assessed by the teachers.Results and discussions: During the community service, three schools were recorded as sehat paripurna and 24 schools as sehat utama. The average value of pre-test and post-test results were 3.52 ± 0.66 and 4.88 ± 0.32, respectively. This indicates that there was an increase in the average value and PHBS counselling may increase participants’ understanding. Additionally, majority of participants agree that the flash cards are suitable for learning purpose.Conclusion: PHBS counselling may provide an understanding of PHBS for elementary school teachers in the Kerjo District, Karanganyar, also, flash cards are applicable for learning purpose.